Anti-obesity effects of Wumeishanzhayin: an integrated lipidomics and transcriptomics study - Huang, Xiao; Liao, Chunling; Peng, Bo; Wang, Jin; Zhang, Yong; He, Qingman; Dang, Sijie; Zhao, Mei (Frontiers in Pharmacology, 2025)
BackgroundThe global prevalence of adult obesity has increased significantly, affecting over 890 million adults worldwide. Wumeishanzhayin (WMSZY), a formulation derived from four medicinal and edible botanical drugs, has shown efficacy in alleviating obesity and lipid metabolism disorders induced by high-fat and high-fructose (HFHF) diets. However, its underlying therapeutic mechanisms remain unclear.ObjectiveThis study aims to investigate the therapeutic effects and mechanisms of WMSZY in ameliorating obesity induced by a HFHF diet.MethodsUPLC-MS/MS was used to characterize the metabolites of WMSZY. The effects of WMSZY on body weight gain, lipid metabolism, and glucose dysfunction were evaluated in a HFHF diet-induced murine model. Targeted lipidomics and transcriptomics analyses were performed to identify differentially altered lipids (DALs) and differentially expressed genes (DEGs). Computational approaches, including molecular docking simulation and dynamics simulations, were used to predict bioactive compound-target interactions. Key findings were validated through RT-qPCR and Western blot. Integrated transcriptomic and lipidomic analyses identified potential therapeutic targets.ResultsSixteen metabolites were identified in WMSZY. Animal studies showed that WMSZY reduced body weight gain, improved lipid and glucose metabolism, and alleviated inflammation in HFHF diet-induced mice. Targeted lipidomics indicated that WMSZY’s anti-obesity effect may be linked to cholesterol metabolism, adipocyte lipolysis, lipid digestion, insulin resistance, and glycerolipid metabolism. Transcriptomic analysis suggested involvement of AMPK, MAPK, and PPAR signaling pathways. Molecular docking simulation revealed strong binding of WMSZY metabolites with AMPK, and simulations showed that cryptochlorogenic acid had notable binding affinity. The data from Western blot and RT-qPCR showed changes associated with the activation of the AMPK/CPT-1 pathway and the inhibition of lipid metabolism-related genes following WMSZY treatment.ConclusionWMSZY significantly reduces body weight gain and ameliorates glucose and lipid metabolic disorders in HFHF diet-induced mice. Its anti-obesity effect is likely due to the regulation of lipid metabolism via the AMPK/CPT-1 signaling pathway.